Economic cycles and periodization of the urban network in Amazonas the cities of Parintins and Itacoatiara – 1655 to 2010 - Schor, Tatiana; Marinho, Thiago Pimentel (Revista do Instituto de Estudos Brasileiros, 2013)
When analyzing the periodization of the urban network in the Amazon different aspects evidence growth and expansion, while others evidence economic stagnation. In any of these cases it is possible to notice the strengthening of certain urban centers, that due to historical-geografical factors, highlight their importance in the urban network of the Amazonas State –Brazil. Aiming to analyse the spatial temporality of the cities of Parintins and Itacoatiara and their role in the urban network along the Amazonas river, this paper presents historical data, results from extensive field work and comprehensive analysis of both cities. This analysis gives new light in the understanding of the urban network in the Brazilian Amazon, considering a different scale to those usually used to understand urbanity in the region.